Analysis of squat shear wall with different dimensions and position of opening under different type of static loads - Ang, Yip Hong (2015)
Shear walls are usually used in high-rise building or building on high frequency of wind area as the structural element to restrain lateral forces. Openings are created on the shear wall for the architecture, ventilation or mechanical and electrical purposes. With the existence of the opening, the strength of the wall is reduced by the reduction in concrete area and the discontinuity of the reinforcement due to opening which may lead to structural failure. The main objective is to study the effect of size and position of the opening towards the structural behavior of the shear wall under different type of static loads. The analysis is done using the software ANSYS12.0. The samples are SW1, SW2, SW3, SW4, SW5, SW6, SW7 and SW8 where SW1 is solid shear wall while SW2, SW3, SW4, SW5, SW6, SW7 and SW8 are shear walls with different size and position of opening. They are analyzed by using 2 different types of loads which are uniformly distributed axial load and uniformly lateral load. From the same magnitude of loads applied towards the shear walls, they are compared by the cracking pattern and the stress distribution. Under both axial and lateral loads, it shows a significance results that the shear wall with greater opening size shows less efficiency. The position of opening further from the support shows a more significance effect towards the strength of the wall from axial load but opposite from the lateral load. Besides, the closer the position of the shear wall to the load, the less efficient it is. As a conclusion from the results, the most suitable position of the opening on the shear wall is further from the support and the loads and it shows that there is a significance effect even from a smallest opening.